The activin‐βA/BMP‐2 chimera AB204 is a strong stimulator of adipogenesis. (15th June 2015) - Kim, Meejung; Kim, Jong In; Kim, Jae Bum; Choe, Senyon
Abstract: Several of the bone morphogenetic proteins (BMPs) have been reported to induce white as well as brown adipogenesis. Here, we characterized the adipogenic potential of AB204, a recombinant chimeric protein of activin‐ β A and BMP‐2, in in vitro, ex vivo and in vivo settings. BMP‐2 is generally known to promote adipogenesis. When compared with BMP‐2, which previously showed varying degrees of adipogenesis, AB204 displayed superior in vitro adipogenic differentiation of mouse 3 T3‐L1 pre‐adipocytes and human adipose‐derived stem cells (hASCs). Surprisingly, implantation of hASCs, preconditioned with AB204 for as short a time as 48 h, into the subcutaneous space of athymic nude mice effectively produced fat pads, but not with BMP‐2. When BMP‐2 and AB204 were injected intraperitoneally, AB204 promoted dramatic systemic adipogenesis of C57BL/6 mice on a high‐fat diet very effectively. The results implicate the novel clinical potential of AB204, including induction of fat tissue ex vivo or in vivo for tissue re‐engineering and regenerative medicinal purposes, more than any known natural protein ligand. Copyright © 2015 John Wiley & Sons, Ltd.